2022
DOI: 10.1111/jgh.15857
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of colonic stent placement for obstructive colorectal cancers: An analysis of short‐term results using a nationwide database in Japan

Abstract: Background and Aims Self‐expandable metallic stent (SEMS) is widely used for obstructive colorectal cancer (OCC). Both SEMS and urgent surgery have several merits and demerits. This study aimed to clarify the efficacy of SEMS by comparing the mortality rate after the hospitalization between SEMS and urgent surgery for OCC. Methods We collected OCC patients' data using the Diagnosis Procedure Combination (DPC) database system. We divided eligible patients into the SEMS and urgent surgery groups using propensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…A previous study showed that application of SEMS as BTS for OLCC seems to be an oncologically safe alternative to emergency resection ( 22 ). SEMS as a BTS for OLCC was associated with lower short-term overall morbidity and lower rates of temporary and permanent stoma ( 23 ), and which can reduce in-hospital death and medical costs compared with emergency surgery ( 24 ). Recent studies have shown that adoption of SEMS as BTS yields favorable long-term oncological outcomes when compared with direct emergency surgery ( 9 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that application of SEMS as BTS for OLCC seems to be an oncologically safe alternative to emergency resection ( 22 ). SEMS as a BTS for OLCC was associated with lower short-term overall morbidity and lower rates of temporary and permanent stoma ( 23 ), and which can reduce in-hospital death and medical costs compared with emergency surgery ( 24 ). Recent studies have shown that adoption of SEMS as BTS yields favorable long-term oncological outcomes when compared with direct emergency surgery ( 9 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analytical studies using this DPC data have been published from various perspectives. (Tarasawa et al 2020;Fujimori et al 2021a, Fujimori et al 2021bFujimori et al 2021c ;Noda et al 2021;Moroi et al 2022) On the other hand, the Japanese National Data Base (NDB) is also managed by the MHLW. NDB focused on the "Act on Securing Medical Care for the Elderly" that collects receipt information from insurers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…We have previously conducted clinical studies on IBD and other lower intestinal tract diseases using the Diagnostic Procedure Combination (DPC) nationwide database. 18 , 19 , 20 , 21 The DPC database contains a large number of admissions and enables analysis of IBD comorbidities, which makes it difficult to collect enough samples for a single‐center study.…”
Section: Introductionmentioning
confidence: 99%